2015
DOI: 10.5194/bg-12-5415-2015
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of benthic foraminiferal Mn / Ca and sedimentary Mn / Al as proxies of relative bottom-water oxygenation in the low-latitude NE Atlantic upwelling system

Abstract: Abstract. Trace element incorporation into foraminiferal shells (tests) is governed by physical and chemical conditions of the surrounding marine environment, and therefore foraminiferal geochemistry provides a means of palaeooceanographic reconstructions. With the availability of high-spatial-resolution instrumentation with high precision, foraminiferal geochemistry has become a major research topic over recent years. However, reconstructions of past bottom-water oxygenation using foraminiferal tests remain i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 57 publications
7
43
0
Order By: Relevance
“…Therefore, the Mn/Ca intra-test variability should ideally not have a diagenetic contribution. The results for all specimens measured in this study showed an average Mn/Ca intra-test variability for A. tepida of 45±15 % (RSD average for all chambers measured on a single specimen; Table A1), which is comparable to that reported in some previous studies (30-50 %; Glock et al, 2012;McKay et al, 2015;Koho et al, 2017). Our results from the different sampling campaigns showed more specimens with higher variability in July compared to March and September (Figs.…”
Section: Intra-test Variability In Elemental Ratios In Benthic Foramisupporting
confidence: 89%
See 4 more Smart Citations
“…Therefore, the Mn/Ca intra-test variability should ideally not have a diagenetic contribution. The results for all specimens measured in this study showed an average Mn/Ca intra-test variability for A. tepida of 45±15 % (RSD average for all chambers measured on a single specimen; Table A1), which is comparable to that reported in some previous studies (30-50 %; Glock et al, 2012;McKay et al, 2015;Koho et al, 2017). Our results from the different sampling campaigns showed more specimens with higher variability in July compared to March and September (Figs.…”
Section: Intra-test Variability In Elemental Ratios In Benthic Foramisupporting
confidence: 89%
“…So far, few studies have investigated the potential of using Mn/Ca ratios in benthic foraminifera as a proxy for bottom water redox state. These studies show that benthic foraminifera register environmental Mn 2+ concentrations in their tests (Reichart et al, 2003;Munsel et al, 2010;Glock et al, 2012;Groeneveld and Filipsson, 2013;Koho et al, 2015Koho et al, , 2017McKay et al, 2015;Barras et al, 2018). For example, Koho et al (2015Koho et al ( , 2017 demonstrated that foraminiferal species occupying a relatively deep microhabitat display higher Mn/Ca ratios than those living near the sediment surface.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations